Klasifikasi Model Percakapan Twitter Mengenai Ujian Nasional - Emilya Ully Artha; Ahmad Dahlan (Politeknik Harapan Bersama, 2018)
The rise of internet usage especially in social media such as Twitter make a possibility to analyze an existing conversations and derived it to various conversation theme. The data was obtained from the Twitter conversation using text mining that is a